Work Motivation, Work Spirit, and Career Development Strategy on Employee Performance - Mersiana Varia Juita; Waloyo Waloyo (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the influence of work motivation, work spirit, and career development strategies on employee performance at PT Maju Jaya Sejahtera, Surabaya. Research Method: A quantitative approach was employed using multiple linear regression analysis. The sample consisted of 70 permanent employees selected through purposive sampling. Data were analyzed to examine the partial and simultaneous effects of the independent variables on employee performance. Results and Discussion: The results indicate that work motivation, work spirit, and career development strategies each have a positive and significant effect on employee performance. Employees with higher motivation tend to be more productive and proactive, while a strong work spirit enhances dedication and resilience in completing tasks. Career development strategies contribute to employee commitment by providing opportunities for skill improvement and professional growth. Simultaneously, the three variables significantly improve employee performance. Implications: The findings suggest that organizations should strengthen employee motivation, foster a positive work environment, and implement effective career development programs to enhance productivity, commitment, and overall organizational performance. Originality: This study contributes to the human resource management literature by examining the combined effects of work motivation, work spirit, and career development strategies on employee performance in the construction industry, offering a more comprehensive perspective on the factors influencing employee effectiveness.